Sketsa Pemikiran Keagamaan dalam Perspektif Normatif, Historis dan Sosial-Ekonomi - Putra, Andi Eka (Universitas Islam Negeri Raden Intan Lampung, 2017)
Contemporary religious thought is open and plural. Various approaches have emerged from the oldest such as the historical approach to the latest such as the Islamic economic approach. various approaches to religious thought are often simply grouped into three main stream groups; namely the normative, historical and sociological groups. These three approaches are not infrequently fragmented, whereas ideally, as a religious thought, the three must be linked and combined to produce a multidisciplinary approach, namely an approach that comprehensively can refresh contemporary religious thought that seems to be sluggish.